Electrospinning fabrication and in situ mechanical investigation of individual graphene nanoribbon reinforced carbon nanofiber. (April 2017) - Li, Xinlu; Yang, Yingchao; Zhao, Yujie; Lou, Jun; Zhao, Xiyu; Wang, Ronghua; Liang, Qinghua; Huang, Zhenghong
Abstract: Graphene nanoribbons (GNRs) with opened edges and less structural defects are embedded in polyacrylonitrile (PAN)-based carbon nanofibers (CNFs) by electrospinning followed by stabilization and carbonization. GNRs not only can be used as one-dimensional nanofillers, but also act as nanoplatelet template to promote the formation of graphitic carbon in PAN matrix. X-ray diffraction, Raman spectroscopy and N2 absorption are used to analyze the microstructure of GNR-reinforced CNFs. In situ tensile test using a micromechanical device inside a scanning electron microscope (SEM) is carried out to evaluate the mechanical performance of individual GNR-reinforced CNF. The tensile strength and elastic modulus of CNFs reinforced by 2 wt% GNRs with a diameter of ∼160 nm are 3.52 GPa and 70.07 GPa, respectively, which are higher than those of pristine PAN CNFs with similar size, i.e. 2.44 GPa and 28.97 GPa. The rough fracture surface for all GNR-reinforced CNFs suggests that the GNRs can dramatically toughen the fibers. A sword-in-sheath failure is observed in 4 wt% GNR reinforced CNFs, confirming that GNRs are entirely embedded and well aligned along the fiber axis. This study demonstrates the potential of GNRs as a promising reinforcement to improve the formation of graphitic carbon and mechanical performance of CNFs. Graphical abstract: